Granular cells in ghost cell odontogenic lesions: an unusual and unexpected finding - Polti, Lucas Fabian; Sicco, Estefanía; Martins-Silveira , Felipe; Frenzel-Schuch , Lauren; Pereira-Prado , Vanesa; Bologna-Molina , Ronell; Paparella, María Luisa (Journal of Oral Diagnosis, 2025)
This study aimed to present two cases of ghost cell odontogenic lesions (GCOL) with granular cells, an unusual finding, in order to contribute to their immunohistochemical characterization and compare results with previous reports. One case corresponded to a calcifying odontogenic cyst (COC) in a 44-year-old man and the other to a dentinogenic ghost cell tumor (DGCT) presenting in an 84-year-old woman. Both lesions were located in the mandible. Microscopically, COC showed a cystic wall lined by ameloblastic/ameloblastomatous epithelium with ghost cells, and DGCT showed ameloblastomatous proliferation with ghost cells and dentinoid/osteodentin matrix. In addition, the presence of cells with abundant granular cytoplasm was observed within the epithelial lining in the cystic lesion and trapped in the dentinoid matrix in the neoplastic lesion. In both cases, the granular cells were positive for AE1-AE3, S100, and CD68; additionally, granular cells in the DGCT were positive for CK19, amelogenin, β-catenin, E-cadherin, vimentin, and lysozyme. The immunohistochemical profile suggests an epithelial origin of granular cells with an increase in lysosomes possibly associated with a degenerative process. Further studies are necessary to clarify the origin of these cells.